1976
DOI: 10.1093/jnci/57.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen in Histopathology: Immunoperoxidase Staining of Conventional Tissue Sections2

Abstract: A triple-bridge, indirect peroxidase-antiperoxidase method for demonstrating carcinoembryonic antigen (CEA) in frozen, ethanol-fixed or formalin-fixed, paraffin-embedded specimens was evaluated. Examination of 359 tissue specimens--234 malignant tumors, 37 benign neoplasms, 41 nonneoplastic diseased tissues, and 47 normal specimens--showed that CEA could usually be demonstrated in a group of cancers. We could detect CEA in carcinomas of the stomach, colon, rectum, pancreas, lung, and cervix. However, malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
74
1
8

Year Published

1977
1977
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(86 citation statements)
references
References 0 publications
3
74
1
8
Order By: Relevance
“…Previously, we reported the immunocytochemical localization of CEA in 66% of colonic carcinomas and 13% of colonic polyps (Goldenberg et al, 1976 Immunoperoxidase procedure.-The immunoperoxidase procedure and the antisera used in this study were described previously (Primus et al, 1975;Goldenberg et al, 1976). Briefly, the tissue sections are incubated sequentially with appropriate dilutions of (1) goat anti-CEA serum or control serum, (2) rabbit anti-goat IgG, (3) goat anti-horseradish-peroxidase, (4) horseradish peroxidase (Sigma, Type VI), (5) 3,3' diaminobenzidine (Sigma, free base), and hydrogen peroxide solution.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Previously, we reported the immunocytochemical localization of CEA in 66% of colonic carcinomas and 13% of colonic polyps (Goldenberg et al, 1976 Immunoperoxidase procedure.-The immunoperoxidase procedure and the antisera used in this study were described previously (Primus et al, 1975;Goldenberg et al, 1976). Briefly, the tissue sections are incubated sequentially with appropriate dilutions of (1) goat anti-CEA serum or control serum, (2) rabbit anti-goat IgG, (3) goat anti-horseradish-peroxidase, (4) horseradish peroxidase (Sigma, Type VI), (5) 3,3' diaminobenzidine (Sigma, free base), and hydrogen peroxide solution.…”
mentioning
confidence: 98%
“…Unfortunately, quantitation of tissue CEA by a radioimmunoassay (RIA) method is not feasible in routine histopathology. Recently, we reported the minimum quantity of tissue CEA required for staining with the 3-layer, peroxidase-antiperoxidase technique (Goldenberg, Sharkey and Primus, 1976 Thus, a decreased sensitivity of CEA detection by immunoperoxidase staining of formalin-paraffin-treated specimens was apparent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far quick-frozen sections, either unfixed or fixed with ethanol, have usually been used for immunofluorescent studies of CEA, although formalin-fixed, paraffinembedded specimens are usable in the immunoperoxidase techniques (Goldenberg, Sharkey and Primus, 1976;Isaacson, 1976). In the present studies we employed ethanol-fixed, paraffin-embedded tissues, and found them to be more satisfactory than frozen sections.…”
Section: Discussionmentioning
confidence: 82%
“…5 At present, measurement of serum CEA levels is mainly used to monitor tumor progression during postsurgery follow-up of patients affected by colorectal cancer. However, it has been demonstrated that about 50% of colorectal cancers are not associated with increased serum CEA levels.…”
mentioning
confidence: 99%